KANDUNGAN TIMBAL CRUSTACEA DI MUARA ANGKE DI SEKITAR TELUK JAKARTA - Maman Rumanta (LPPM Universitas Terbuka, 2005)
The study was conducted to observe concentration of lead on Crustacean as a marine product of Muara Angke’s traditional fisherman of Jakarta Bay. Four species of Crustacean were selected as sample. Each sample was triple and collected in four sampling periods, east monsoon, transition period from east to west monsoon (transition period I), west monsoon, and transition period from west to east monsoon (transition period II). Lead concentrations of collected samples were tested using flame-AAS. The result indicated that lead concentration on meat of Crustacean was lower than the concentration on carapaces and gills. But each of the concentration was higher than maximum level proposed by CCFAC (1999). Commonly the concentration of lead on Crustacean especially on meat and gills were high during east monsoon, but low during west monsoon.